2017
DOI: 10.15587/1729-4061.2017.101736
|View full text |Cite
|
Sign up to set email alerts
|

Research into processes of wastewater treatment at plants of meat processing industry by flotation and coagulation

Abstract: Among industrial enterprises, which heavily pollute the environment, the impact of food industry companies is significant. First of all, it concerns enterprises that process agricultural raw materials, especially those of cattle-breeding. These enterprises are characterized not only by high water consumption (they occupy one of the first places among other industries), but also by significant dumping of used and contaminated wastewater into the environment: water, soil, and atmosphere. Some of these enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Under the influence of ultrasound, complex physical and chemical processes occur in the aquatic environment that contribute to the oxidation of organic substances and reduction of COC, the structuring, compaction, and agglomeration of sediment, etc. Work [12] shows the positive effect of preliminary ultrasonic treatment of Са(ОН) 2 suspension on the process of coagulation treatment of wastewater from meat processing enterprises. The efficiency of the COC process, depending on the concentration and dose of acoustically treated Са(ОН) 2 , increased by 1.3...4.5 times.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Under the influence of ultrasound, complex physical and chemical processes occur in the aquatic environment that contribute to the oxidation of organic substances and reduction of COC, the structuring, compaction, and agglomeration of sediment, etc. Work [12] shows the positive effect of preliminary ultrasonic treatment of Са(ОН) 2 suspension on the process of coagulation treatment of wastewater from meat processing enterprises. The efficiency of the COC process, depending on the concentration and dose of acoustically treated Са(ОН) 2 , increased by 1.3...4.5 times.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It was shown that when using ultrasound, it was possible to significantly reduce the interaction time and the amount of Ca(OH) 2 suspension. The positive effect of the use of ultrasound was also shown in the treatment of wastewater from meat processing enterprises (Savchuk et al, 2017). To reduce the cost of coagulation wastewater treatment, coagulants obtained from waste from other industries are used (Vasiichuk et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…In accordance with the goals of sustainable development where the priority is environmental improvement and conservation of natural resources a 3R waste management strategy (Reduction, Reuse, Recycling) will be effective, that is we consider waste as available resources (Madadian et al, 2020;Savchuk et al, 2017;Kurylets et al, 2022). Therefore, technologies for processing secondary organic waste into useful secondary raw materials will help to improve the functioning of the circular economy (European Commission, 2018;Vanhamäki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%